Improving the Ability in Academic Writing of Student’s English Education Department Through Self Directed E-Learning - Yulia Rizki Ramadhani; Rini Kesuma Siregar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
The aim of this study is to collaborate on the Self Directed Learning model through the use of moodle technology media in which the learning model can enhance the quality and effectiveness of student learning independently so that students can use technology devices in a correct and proper way. This study utilizes a quantitative approach to the design of OneGroup Pretest-Posttest Design with a pre-experimental research technique. The researcher used cluster samples in the process of collecting samples. The data collected from this study was further analyzed and conclusions were reached using the Prerequisite Test of Analysis and the Paired T-Test Test for hypotheses. The findings of the study with the descriptive statistical analysis showed that the pre-test average value was lower than the post-test average, in description there were differences in the average learning outcomes between the pre-test and post-test. Based on the results of the Paired T-Test statistics, Ha is accepted as having  t-count value (13,691) greater than T-table (2,131). The results of the pre-testand post-testing are differenced on average so there is a significant effect of self-directed learning using moodle to improve student learning achievement in academic writing skills. The average value of the experimental class was included in a sufficient category, according to calculated results from Gain-scores. It means learning through self-directed e-learning is quite effective in order to improve students ' academic writing abilities. Self-directed learning through Moodle and learning resources are quite effective and efficient in improving student learning and can encourage students to learn on-campus as well as at home, train students to be ready for learning, allow students to participate actively during face to face teaching and learning activities so that students can enhance learning outcomes.